How Do Fractures Influence Hyporheic Exchange in Sedimentary Rock Riverbeds?. Issue 7 (21st July 2021) - Chow, R.; Parker, B. L.; Steelman, C. M.; Thoms, A.; Nowak, W.
Abstract: Bedrock rivers represent a hydrogeological environment in which surface water flows along an exposed bedrock surface. Studies of hyporheic exchange have exclusively involved rivers composed of unconsolidated fluvial sediments, leaving a critical knowledge gap. This study evaluates the conditions that could support bedform‐scale hyporheic exchange within a fractured sedimentary bedrock river based on field data collected near Guelph, Canada. Hyporheic exchange at the bedform‐scale was evaluated by numerically modeling the migration of a conservative solute tracer through a bedrock riverbed within a two‐dimensional vertical cross‐section along the flow direction. A stochastic discrete fracture‐matrix framework was developed to represent measured subsurface fractured bedrock properties, producing a probabilistic distribution of potential hyporheic exchange pathways. Flow and transport model results indicate that: (a) bedform‐scale hyporheic exchange within a bedrock river exists with high fluid flow velocities in fractures, yet long solute residence times due to diffusion across the fracture‐matrix boundary; (b) the coincidence of fractures and hydrodynamic head gradients across the riverbed controls the spatial extent of bedform‐scale hyporheic exchange; and (c) the potential variability in hyporheic exchange residence time is large (i.e., tens of years) due to the inherent variability in facture network properties. Our field‐based numerical study indicates that the average (median) residence time may not be a good proxy for the potential natural attenuation capacity of a fractured sedimentary bedrock riverbed and that hyporheic exchange has the potential to emplace surface water contaminants within the fractured porous rock matrix that could become a long‐term source of trace contaminants. Key Points: Hyporheic exchange is possible at the bedform‐scale within fractured sedimentary bedrock rivers Solute residence times will be orders of magnitude slower compared to a riverbed composed of unconsolidated sediments Coincidence of fracture connectivity and hydrodynamic head gradients controls spatial extent of bedform‐scale hyporheic exchange